2011
DOI: 10.31018/jans.v3i2.175
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of black velvet tamarind (Dialium guineense Willd) seedling to different potting media

Abstract: :The response in growth and development of seedlings of Dialium guineense to different potting media was studied in the screen house. Five potting media: River sand (Rs), Top soil (Ts), Poultry manure (Pm), Rice husk (Rh) and Oil palm refuse bunch (OPRB) were used. They were evaluated as sole treatments and in combination with river sand (Rs) in different ratios (1:1, 1:2, 2:5 and 5:2) respectively. All together, twenty -one (21) potting media types were evaluated. The experiment was laid out in a completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…The differences in the nutrient composition of the media sources may be due to variation in the organic matter content in the different component of the growth media. Similar differences in nutrient composition were reported by Osaigbovo and Nwaoguala (2011) for growth sources used for raising seedlings of Dialium guineense.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The differences in the nutrient composition of the media sources may be due to variation in the organic matter content in the different component of the growth media. Similar differences in nutrient composition were reported by Osaigbovo and Nwaoguala (2011) for growth sources used for raising seedlings of Dialium guineense.…”
Section: Resultssupporting
confidence: 82%
“…Five of the media sources were slightly acidic with a pH range of 5.68 -6.50, while media with sole cocoa husk (Ch) and cocoa husk (Ch) plus rice husk (Rh) (Ch +Rh 1:1) were with pH 7.20 and 7.40 respectively. Osaigbovo and Nwaoguala (2011) reported slight acidity with pH range of 5.11 -6.20 for the potting media sources used to raise Dialium guineense. Khan et al (2006) recommended that the media pH value for container grown plant should be slightly acidic (5.5 -6.5).…”
Section: Resultsmentioning
confidence: 99%
“…As in this experiment, the lowest diameter and height of shoots of tamarind (Dialium guineense Willd) were found with treatments of distinct proportions of river sand and rice husk (1:1, 1:2, 2:5 and 5:2) [33]. This suggests that rice husk may interfere with the growth of tamarind, as well as citrus as our data shows.…”
Section: Height and Diametersupporting
confidence: 47%
“…It was obviously found that different soil media in various combinations has different, descriptive and analytical effects on root dry weight. The better performance of seedling root dry weight could be due to improvement of physical status such as less compactness and increased aeration of the medium (Osaigbovo and Nwaoguala, 2011). Organic matter has also been described to resist compaction and to maintain water while maintaining air and root growth as described (Khan et al, 2006).…”
Section: Root Dry Weightmentioning
confidence: 99%